Exploring generational cohorts’ engagement in voluntary simplistic clothing consumption practices in the South African emerging market context - Sonnenberg, Nadine Cynthia (University of Pretoria, 2024)
Dissertation (MConsumer Science (Clothing Retail Management))--University of Pretoria, 2023.